2007
DOI: 10.1038/bdj.2007.679
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of first permanent molar teeth: results from three dental hospitals

Abstract: • Caries is the main reason for the extraction of first permanent molars in children.• Children who are attending dental hospitals for extraction of first permanent molars tend to be older than the optimal age for achieving space closure.• There is a need for guidelines advising primary care dentists when to refer children for the extraction of fi rst permanent molars.• This study highlights the need for extensive prevention programmes targeted at those children with high caries risk.Extraction of first perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
2
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 12 publications
0
50
2
13
Order By: Relevance
“…Albadri et al [24] reported similar findings, in which children who underwent FPM extractions were older than the age allowing optimal spontaneous space closure.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Albadri et al [24] reported similar findings, in which children who underwent FPM extractions were older than the age allowing optimal spontaneous space closure.…”
Section: Discussionmentioning
confidence: 74%
“…In one report, the principal indication for extraction of FPM was extensive caries (70%) followed by hypomineralization of the molar incisors (11%) [24]. Accordingly, in our systematic review, we included studies that addressed the consequences of early extraction of “compromised FPMs”, i.e., FPMs with severe caries or hypomineralization.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, neg ative consequences of the extraction of the first permanent molars are numerous, and primarily conditioned by the number and time of their extraction. The research by Albadri 15 et al has shown that even in 70% of cases, caries with bad prognosis is the reason for the extraction of the first permanent molars, and in 11% of cases that is molar-incisor hypomineralization. In addition, this group of authors suggested that the average time of the first permanent molars extraction is the age of 11, which is substan tially later than the time recommended in case when the extraction of these teeth is necessary, and that is the age between year 8 and 10 16 .…”
Section: Zaključakmentioning
confidence: 99%
“…However, it has been suggested that there is little evidence to support this being a significant risk [8]. Furthermore, the extraction of an additional FPM places an increased burden on both the child and the dental team providing care for them, and may tip the balance of decision as to whether the extractions can be carried out under local anesthesia, towards favoring dental general anesthesia [9]. …”
Section: Introductionmentioning
confidence: 99%